Let’s talk mental health: analysis of Indian immigrant women’s culturally centered mental health perceptions and identifying modifiers in interventions - Bhati, Sakshi (Kansas State University, 2024)
Mental health problems such as depression and anxiety are common among immigrant groups in the United States. Differences in cultural values and practices inform the variety of mental health perceptions and behaviors. Negative perceptions and barriers persist among Indian immigrant women due to stigma and fear of judgment. Although previous research has documented the prevalence of mental health diseases among Indian immigrant women, there is a limited understanding of the role of Indian culture in influencing perceptions and help-seeking behaviors. This hinders improvement in interventions and campaigns for cultural communities. To fill these gaps, this health communication research aimed to develop a thorough understanding of how culture shapes mental health perceptions and help-seeking behaviors among Indian immigrant women and to elicit recommendations for enhancement in the current intervention from community mental health experts. Using Hofstede’s cultural determinants theory, culture-centered approach, and collective leadership as a theoretical framework, this study employed a hermeneutic phenomenological approach using in-depth semi-structured interviews among Indian immigrant women and focus group discussion among mental health experts. Findings indicated that the Indian culture negatively influences perceptions and behaviors among Indian immigrant women. Masculinity, collectivism, high power distance, and uncertainty avoidance restrict women’s mental health expression and ability to seek help. Further, Indian immigrant women’s lived experiences, along with cultural and social factors, shape their perceptions. Additionally, acculturative experiences hinder mental well-being but also improve Indian immigrant women’s outlook on diseases and treatments. These women also perceive contextual and cost-related barriers while also facing difficulty in communicating about mental health due to a lack of awareness and openness among other Asian Indians. To address these challenges, mental health experts elicited recommendations for mental health experts to be proactive in the immigrant communities. They also provided enhancement opportunities for universities to improve their accessibility for international and immigrant communities and train future therapists to become more culturally attuned. Additionally, cultural ambassadorship must be adopted to reach immigrant communities through leaders. The theoretical and practical implications of this research are highlighted in the study. The study suggests further research in understanding the role of culture in mental health topics among minority groups with the use of culture-centered approach that can accentuate development in health interventions. It provides avenues for social change scholarship in health topics that can look beyond Western biomedicine. The study concludes by presenting an overview of the completion of research goals.
Keywords: Culture centered approach; Health communication; Collective leadership; Hermeneutic phenomenology; Hofstede's cultural determinants; Indian immigrant women